Effect of alumina particle morphology used for air abrasion on loss of enamel and luting composite resin. Issue 12 (December 2021) - Türp, Lisa; Bartels, Nomi; Wille, Sebastian; Lehmann, Frank; Kern, Matthias
Highlights: Surface effects of alumina particle air abrasion depends strongly on particle morphology. Air abrasion with 85 μm round-shaped alumina particles is minimally invasive to enamel. Round-shaped alumina particles might be suitable when removing composite remnants. Air abrasion with 50 μm sharp-edged alumina particles results in significant volume loss of enamel. Abstract: Objective: To evaluate the volume loss after air abrasion with alumina particles with different morphology on bovine enamel and luting composite resin. Methods: Air abrasion was performed on 12 unscathed bovine teeth and 72 luting composite resin discs with 85 μm round-shaped and 50 μm sharp-edged alumina particles applied for 20 s, 40 s and 60 s (n = 12). Air abrasion was standardized by uniform areas of 2 mm diameter, a pressure of 0.25 MPa and a distance of 3 mm. The volume loss was determined by using a laboratory scanner. Results: Air abrasion with round-shaped alumina particles was mostly not measurable with the laboratory scanner, while sharp-edged alumina air abrasion resulted in significant loss of enamel. The median of volume loss by sharp-edged alumina particles ranged from 0.78 mm 3 (20 s) to 2.52 mm 3 (60 s). In contrast to round-shaped alumina the removal caused by sharp-edged alumina increased significantly with increasing application times (p ≤ 0.05). For air abrasion on luting composite resin the median of the removed volume ranged from 2.25 mm 3 (20 s) to 6.18 mm 3 (60 s), while round-shaped alumina showed a range from 0.45 mm 3 (20 s) to 1.40mm 3 (60 s). The round-shaped alumina produced a statistically significant lower volume loss than sharp-edged alumina for all three air abrasion times. Significance: The 85 μm round-shaped alumina particles removed less composite resin than 50 μm sharp-edged alumina particles but barely any enamel, making it an option for removing composite resin residues from enamel.